Investigating the Effect of Enzymatically-Derived Blackcurrant Extract on Skin Staphylococci Using an In Vitro Human Stratum Corneum Model - Marija Ćorović; Anja Petrov Ivanković; Ana Milivojević; Klaus Pfeffer; Bernhard Homey; Patrick A. M. Jansen; Patrick L. J. M. Zeeuwen; Ellen H. van den Bogaard; Dejan Bezbradica (Pharmaceutics)
Background/Objectives: Numerous intrinsic and extrinsic stressors can disrupt the balance of the skin microbiome, leading to the development of various skin diseases. It has been proven that coagulase-negative staphylococci (CoNS) are important commensals for maintaining skin microbiome homeostasis and fighting cutaneous pathogens such as Staphylococcus aureus (S. aureus). Here, we examined the influence of polyphenol-rich enzymatic blackcurrant extract (EBCE) on pathogenic coagulase-positive S. aureus strains and beneficial CoNS, like Staphylococcus epidermidis (S. epidermidis), to explore its potential for rebalancing the skin microbiota. Methods: The polyphenol profile of EBCE was determined by ultra-high-pressure liquid chromatography–tandem mass spectrometry. Microwell plate assays were employed to study the effect of EBCE on five S. aureus strains isolated from the skin of atopic dermatitis patients. An in vitro human stratum corneum model was used to test its effect on mixed bacterial cultures. Results: EBCE inhibited the growth of all tested S. aureus strains by 80–100% at the highest tested concentration after 7 h. No microbial growth was observed at the highest tested EBCE concentration using the stratum corneum model inoculated with one selected pathogen (S. aureus SA-DUS-017) and one commensal laboratory strain (S. epidermidis DSM 20044). The lowest tested concentration did not interfere with S. aureus growth but strongly stimulated the growth of S. epidermidis (~300-fold colony forming unit increase). In addition, low EBCE concentrations strongly stimulated CoNS growth in microbiome samples taken from the armpits of healthy volunteers that were spiked with S. aureus SA-DUS-017. Conclusions: These preclinical data support further testing of EBCE-enriched topical preparations as potential cutaneous prebiotics in human studies.